Equity valuation: Hewlett Packard Enterprise - Silva, Tiago Rodrigues Correia e (2023)
This study aimed to determine the fair value of Hewlett Packard Enterprise (HPE) stock on October 31, 2022. By comparing the actual market value with the predicted fair value, the goal was to identify market undervaluation or overvaluation. Investors can measure if the market price aligns with intrinsic value by comparing estimated fair value to actual market value. A higher projected fair value could suggest undervaluation, offering investment opportunities. Conversely, a lower projected fair value might signal overvaluation, urging caution in investment choices. This research sheds light on HPE's market perception, aiding informed investment decisions. It underscores the need to scrutinize the company's underlying value and comprehend market valuation to uncover investment potential or prudence during overvaluation. HPE is a technology company focused on intelligent solutions, spanning Compute, HPC & AI, Storage, Intelligent Edge, FS, Corporate Investments and Other segments. This thesis examines HPE's valuation using DCF (FCFF-based) and Relative Valuation methods. It involves meticulous evaluation of company projections, historical performance, macroeconomic climate, and industry trends. These methodologies and assumptions aim to provide a comprehensive and precise evaluation of HPE's intrinsic value. The two methods used yield different conclusions, yet the DCF analysis indicates that, on October 31st, 2022, HPE's share price was undervalued by roughly 34,24%.